Effect of Density on Acoustic and Thermal Properties of Low-Density Particle Boards Made from Agro-Residues: Towards Sustainable Material Solutions - Kiran Maladevihalli Chandroji Rao; Mamatha Baballi Sheshagiri; Ramkumar Velayutham Ramamoorthy; Mugahed Amran; Anand Nandanwar; Prakash Vijayakumar; Siva Avudaiappan; Pablo Guindos (BioResources)
This study assessed the feasibility of using major agricultural residues specifically bagasse, rice straw, wheat straw, and coir fiber to produce single-layer particle boards. These boards of densities 300, 400, and 500 kg/m³ were developed using melamine urea formaldehyde resin. Comprehensive evaluation of the boards included determination of their sound absorption coefficient (SAC), thermal conductivity, and noise reduction coefficient (NRC), as well as various physical properties and modulus of rupture. Additionally, the impact of board density on the SAC across a frequency range of 50 to 5000 Hz was examined. The coir boards displayed superior SAC, particularly at 3000 Hz. Rice straw boards at a density of 300 kg/m³ exhibited the lowest thermal conductivity (0.098 W/m-K). Density of 300 kg/m³ was optimal for achieving the highest SAC and lowest thermal conductivity in agro residue particle boards. As the density of the boards increased, SAC decreased, whereas thermal conductivity (K) increased, indicating that lower-density boards are more effective as sound and thermal insulators. Furthermore, all particle boards demonstrated promising sound absorption capabilities, achieving classifications of D and E under ISO 11654:1997, making them viable for interior applications in the building industry.